Dietary Intake and Type 2 Diabetes - Ojo, Omorogieva (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The prevalence of diabetes is on the increase in the UK and worldwide, partly due to changes in lifestyle which predispose individuals to overweight and obesity. It is estimated that about 90% of the currently diagnosed adults have type 2 diabetes, and based on the World Health Organisation (WHO) report, about 422 million adults were living with diabetes in 2014 compared with 108 million in 1980; this condition caused about 1.5 million deaths in 2012. In the United States of America, it is estimated that about 30.3 million adults are living with diabetes, with a further 1.5 million new diabetes cases diagnosed every year, representing an increasing prevalence of this condition. Diabetes represents a major public health challenge, despite advances in technology and the pharmaceutical industry. These problems may be in the form of acute or long-term complications. Therefore, in order to attenuate the problems of diabetes, management strategies usually include lifestyle changes such as increased physical activity and dietary interventions. Studies which evaluate the role of nutrition in the management of type 2 diabetes often involve human and animal models as these approaches enable us to have a broader and more in-depth understanding of the condition. In some cases, diabetes may co-exist with other conditions, such as stroke, and these may present unique challenges with regard to nutritional interventions. This Special Issue aims to evaluate the risk factors associated with type 2 diabetes and the role of the diet in the management of people with this condition. This evidence is drawn from both human and animal studies.